(untitled) (Journal of Nobel Medical College, 2018)
Introduction: Rheumatic heart disease (RHD) is a common cardiac problem. Medical therapy is directed toward secondary prophylaxis and supportive treatment for heart failure (HF), rhythm disorder and anticoagulation to prevent thromboembolism. Drug utilization patterns thus provide a favorable feedback to physicians and help to modify treatment strategies. Materials and Methods: This is a cross sectional study on 140 patients with RHD who received care at Nobel Medical College Teaching Hospital from October 2017 to September 2018. A semi structured questionnaire was administered to record the demographic characteristics, co-morbid conditions and use of different drugs. Results: Mean age was 50.09 ± 10.99 years. RHD was more common in females (75.7%). Penicillin prophylaxis was prescribed for 38 (27.1%) patients. Out of which, 22.8% were on daily oral penicillin and 4.2% were receiving three weekly benzathine benzylpenicillin. Beta blockers were the most frequently used drug for heart rate control for patients (51.4%) with both atrial fibrillation (AF) and/or symptomatic mitral stenosis (MS). Digoxin was used in 10% and calcium channel blockers were used in 3.5% of patients who have AF. Different diuretics were used in 88.5% of patients with features of systemic or pulmonary congestion. Out of 20 cases of AF, eleven (55%) were receiving aspirin and nine (45%) were on oral anticoagulants. Out of nine patients receiving warfarin, only four (20%) had therapeutic international normalized ratio (INR). Conclusions: This study focuses on prescription pattern of drugs for different indications in patients with RHD. There is a need for improved use of secondary prophylaxis to prevent recurrence of RF and antithrombotic in patients with AF.